2008
DOI: 10.1182/blood-2007-11-115204
|View full text |Cite
|
Sign up to set email alerts
|

Notch-dependent control of myelopoiesis is regulated by fucosylation

Abstract: Cell-cell contact–dependent mechanisms that modulate proliferation and/or differentiation in the context of hematopoiesis include mechanisms characteristic of the interactions between members of the Notch family of signal transduction molecules and their ligands. Whereas Notch family members and their ligands clearly modulate T lymphopoietic decisions, evidence for their participation in modulating myelopoiesis is much less clear, and roles for posttranslational control of Notch-dependent signal transduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 72 publications
10
77
0
Order By: Relevance
“…On the one hand, some in vitro studies show that activated Notch signaling inhibits differentiation of myeloid precursors [147 -149]. This is also supported by a recent work using a conditionally induced null mutation in the FX locus, that results in a myeloproliferative phenotype [150]. FX encodes an essential enzyme in the GDP-fucose synthesis pathway.…”
Section: Notch and B-cell Developmentmentioning
confidence: 87%
“…On the one hand, some in vitro studies show that activated Notch signaling inhibits differentiation of myeloid precursors [147 -149]. This is also supported by a recent work using a conditionally induced null mutation in the FX locus, that results in a myeloproliferative phenotype [150]. FX encodes an essential enzyme in the GDP-fucose synthesis pathway.…”
Section: Notch and B-cell Developmentmentioning
confidence: 87%
“…To evaluate out the potential importance of Notch 1 signaling in pulmonary fibrosis, the effects of deficiency in Notch signaling in FX Ϫ/Ϫ mice without exogenous fucose supplementation was examined. 47 Because Notch signaling is required for normal development, the use of KO animals deficient in this critical function is not feasible for studies to demonstrate its in vivo importance in fibrosis. The availability of the FX Ϫ/Ϫ mouse affords a means to study this because Notch deficiency is only evident if the animals are deprived of fucose in their diet, ie, this is effectively a conditional KO.…”
Section: Discussionmentioning
confidence: 99%
“…Because fucosylation is essential for Notch function, in the absence of exogenous fucose, Notch signaling is deficient in these animals. 47 The de novo appearance of myofibroblasts and their persistence are key features for progressive fibrotic diseases. 21 Our data showed that after BLM treatment, significantly reduced pulmonary fibrosis in Notch-deficient mice was observed with decreased ␣-SMA expression and collagen deposition, suggesting a reduction in genesis of myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The O-fucosyltransferase, Pofut, mutant mice are viable but display T cell deficiency as a result of reduced Notchligand interaction and signaling (Ge and Stanley, 2008;Zhou et al, 2008). Two other reports using a zebrafish and a fucosylation loss of function mouse model, show that neuronal development and neuronal plasticity are affected, likely through impairment in Notch signaling (Song et al, 2010;Yagi et al, 2012).…”
Section: Translational and Post-translational Regulationmentioning
confidence: 99%